Network influence effects in agent-based modelling of civil violence - Lemos, C. M.; Hélder Coelho; Coelho, H.; Lopes, R. J. (Advances in Social Simulation 2015. Advances in Intelligent Systems and Computing, 2015)
In this paper we describe an agent-based model of civil violence with network influence effects. We considered two different networks, ‘family’ and ‘news’, as a simplified representation of multiple-context influences, to study their individual and joint impact on the size and timing of violence bursts, the perceived legitimacy, and the system’s long term behaviour. It was found that network influences do not change either the system’s long term behaviour or the periodicity of the rebellion peaks, but increase the size of violence bursts, particularly for the case of strong ‘news impact’. For certain combinations of network influences, initial legitimacy, and legitimacy feedback formulation, the solutions showed a very complicated behaviour with unpredictable alternations between long periods of calm and turmoil.